2013
DOI: 10.1016/j.cgh.2013.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Management of Gastric Polyps: An Endoscopy-Based Approach

Abstract: The endoscopic finding of a gastric polyp and the histopathologic report that follows may leave clinicians with questions that have not been addressed in formal guidelines: do all polyps need to be excised, or can they just be sampled for biopsy? If so, which ones and how many should be sampled? What follow-up evaluation is needed, if any? This review relies on the existing literature and our collective experience to provide practical answers to these questions. Fundic gland polyps, now the most frequent gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 72 publications
2
81
0
3
Order By: Relevance
“…A large US study found that the relative prevalence of fundic gland polyp was 77% amongst 7877 gastric polyp [29]. In addition, we confirmed that the prevalence of these benign polyps is significantly higher in H. pylori negative patients, and in those taking PPI therapy, as pointed out in literature [30].…”
Section: Discussionsupporting
confidence: 83%
“…A large US study found that the relative prevalence of fundic gland polyp was 77% amongst 7877 gastric polyp [29]. In addition, we confirmed that the prevalence of these benign polyps is significantly higher in H. pylori negative patients, and in those taking PPI therapy, as pointed out in literature [30].…”
Section: Discussionsupporting
confidence: 83%
“…The results of the present study indicated that the formation of fundic gland polyps and adenomatous polyps had a weak relationship with Hp infection, which was consistent with the results of the previous study (2). Worldwide, it seems that the incidence of Hp infection has an influence upon the types of polyps found in different populations in the west; as Hp infection decreases, fundic gland polyps increase, while in areas such as East Asia, where Hp infection remains common, hyperplastic or neoplastic polyps related to the underlying inflammatory process are more common (18). The level of Hp infection is important because it is an established risk factor for gastric cancer (19), and Hp eradication therapy can effectively reduce the development of precancerous lesions and gastric cancer (20).…”
Section: Discussionsupporting
confidence: 81%
“…The cancerous rate of GPs in males was higher in males than in females; this may be because adenomatous polyps are more common in males than in females, and the malignancy of GPs is closely related to adenomatous polyps. In terms of the risk of developing gastric cancer in the current population, further studies would need to be performed on these patients in the future; however, it is fairly well established that adenomas are precursors for gastric adenocarcinoma, and while the risk of gastric cancer from hyperplastic polyps may be less than 2%, it remains worthy of consideration (18). It has been reported that pathological types of polyps differ with different ages (1,8).…”
Section: Discussionmentioning
confidence: 99%
“…If the lesion is too large or resection is unable to be performed, biopsies of the lesions should be taken, and if dysplasia is present or the biopsy is inadequate to exclude dysplasia, then the patient should be referred for surgical wedge resection, which may be able to be done laparoscopically if the endoscopist has previously tattooed the lesion or lesions. 35 According to American Society for Gastrointestinal Endoscopy guidelines, these lesions should undergo surveillance 1 year after initial resection and then at intervals of no more than every 3 to 5 years. If initial pathology is negative for dysplasia, then no further surveillance is necessary.…”
Section: Nonneoplastic Gastric Polyps: Gastric Hyperplastic Polypsmentioning
confidence: 99%